Semantic web services theory, tools, and applications - Cardoso, Jorge 1970- (Hershey, Pennsylvania Information Science Reference, 2007)
Brings together researchers, scientists, and representatives from different communities to study, understand, and explore the theory, tools, and applications of the semantic Web. Joins the semantic Web, ontologies, knowledge management, Web services, and Web processes into one fully comprehensive resource, serving as the platform for exchange of both practical technologies and research.
The syntactic and the semantic web / Jorge Cardoso -- Logics for the semantic web / Jos de Bruijn -- Ontological engineering / Oscar Corcho, Mariano Fernandez-Lopez, and Asuncion Gomez-Perez -- Editing tools for ontology creation / Ana Lisete Nunes Escorcio and Jorge Cardoso -- Web ontology languages / Grigoris Antoniou and Martin Doerr -- Reasoning on the semantic web / Rogier Brussee and Stanislav Pokraev -- Introduction to web services / Cary Pennington ... [et al.] -- Service-oriented processes / Chun Ouyang ... [et al.] -- Semantic web services / Rama Akkiraju -- The process of semantic annotation of web services / Christoph Ringelstein, Thomas Franz, and Steffen Staab -- Semantic web service discovery / Vassileios Tsetsos, Christo Anagnostopoulos, and Stathes Hadjiefthymiades -- Semantic web service discovery in the WSMO framework / Uwe Keller ... [et al.] -- Semantic search engines based on data integration systems / Domenico Beneventano and Sonia Bergamaschi.
Keywords: Semantic Web; Web services; Electronic books